Reversal of right ventricular pressure loading improves biventricular function independent of fibrosis in a rabbit model of pulmonary artery banding. (21st July 2022) - Fujioka, Tao; Akazawa, Yohei; Ide, Haruki; Karur, Gauri Rani; Bannan, Badr; Grosse‐Wortmann, Lars; Sun, Mei; Hui, Wei; Slorach, Cameron; Honjo, Osami; Friedberg, Mark K.
Abstract : Abstract: Right ventricular (RV) pressure loading leads to RV and left ventricular (LV) dysfunction through RV hypertrophy, dilatation and fibrosis. Relief of RV pressure load improves RV function. However, the impact and mechanisms on biventricular reverse‐remodelling and function are only partially characterized. We evaluated the impact of RV pressure overload relief on biventricular remodelling and function in a rabbit model of reversible pulmonary artery banding (PAB). Rabbits were randomized to three groups: (1) Sham‐operated controls ( n  = 7); (2) PAB (NDef, n  = 7); (3) PAB followed by band deflation (Def, n  = 5). Sham and NDef animals were sacrificed at 6 weeks after PAB surgery. Def animals underwent PAB deflation at 6 weeks and sacrifice at 9 weeks. Biventricular geometry, function, haemodynamics, hypertrophy and fibrosis were compared between groups using echocardiography, magnetic resonance imaging, high‐fidelity pressure‐tipped catheters and histology. RV pressure loading caused RV dilatation, systolic dysfunction, myocyte hypertrophy and LV compression which improved after PAB deflation. RV end‐diastolic pressure (RVEDP) decreased after PAB deflation, although remaining elevated vs . Sham. LV end‐diastolic pressure (LVEDP) was unchanged following PAB deflation. RV and LV collagen volumes in the NDef and Def group were increased vs . Sham, whereas RV and LV collagen volumes were similar between NDef and Def groups. RV myocyte hypertrophy ( r  = 0.75, P  < 0.001) but not collagen volume was related to RVEDP. LV myocyte hypertrophy ( r  = 0.58, P =  0.016) and collagen volume ( r  = 0.56, P =  0.031) correlated with LVEDP. In conclusion, relief of RV pressure overload improves RV and LV geometry, hypertrophy and function independent of fibrosis. The long‐term implications of persistent fibrosis and increased biventricular filling pressures, even after pressure load relief, need further study. Key points: Right ventricular (RV) pressure loading in a pulmonary artery banding rabbit model is associated with RV dilatation, left ventricular (LV) compression; biventricular myocyte hypertrophy, fibrosis and dysfunction. The mechanisms and impact of RV pressure load relief on biventricular remodelling and function has not been extensively studied. Relief of RV pressure overload improves biventricular geometry in conjunction with improved RV myocyte hypertrophy and function independent of reduced fibrosis. These findings raise questions as to the importance of fibrosis as a therapeutic target. Abstract : Abstract figure legend The impact of RV pressure overload relief on biventricular remodelling and function in a rabbit model of reversible pulmonary artery banding (PAB) was evaluated. Rabbits were randomized to three groups: (1) Sham‐operated controls; (2) PAB (NDef); (3) PAB followed by band deflation (Def). Biventricular geometry, function, haemodynamics, hypertrophy and fibrosis were compared between groups using echocardiography, magnetic resonance imaging (MRI), high‐fidelity pressure‐tipped catheters and histology. RV pressure loading caused RV dilatation, systolic dysfunction, myocyte hypertrophy and LV compression which improved after PAB deflation. RV end‐diastolic pressure (RVEDP) decreased after PAB deflation, although remaining elevated vs . Sham. RV and LV collagen volumes in the NDef and Def group were increased vs . Sham, whereas RV and LV collagen volumes were similar between NDef and Def groups. RV myocyte hypertrophy ( r  = 0.75, P  < 0.001) but not collagen volume was related to RVEDP. In conclusion, relief of RV pressure overload improves RV and LV geometry, hypertrophy and function independent of fibrosis.